Sistem Pertukaran Orang Sasak dalam Prosesi Sorong Serah Ajikrame - Fauzan, Ahmad (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2018)
Sasak people Trasaksionalisme we can find on the procession merariq which there are series of processions such as ajikrama handover , we make it as the object in “social exchange”. So in the procession of Sasakajikrama handover is a binding kinship transaction between the family of the prospective groom and bride. Keyword: ajikrama handover, merariq (marriage), exchange, transaksionalime, sasak people.